POLA KOMUNIKASI SATU ARAH SEBAGAI INTERAKSI EDUKATIF DALAM KISAH NABI ĀDAM AS - Ahmad Yunus Mokoginta Harahap (TA'LIM : Jurnal Studi Pendidikan Islam, 2022)
Educational interaction is a relationship between two or more people in the educational process. The interaction will form a pattern of one-way, two-way and even multidirectional communication. In the story of the Prophet Adam AS in the Qur'an there is an educational interaction that forms a pattern of one-way communication. This study aims to find one-way communication patterns as educational interactions in the story of the Prophet Adam AS. The research method used is a type of library research (library Research). The data source comes from the primary data source in the form of verses from the Qur'an about the story of the Prophet Adam, and the secondary data source comes from an interpretation book about the opinions of scholars. Data analysis using content analysis. As a result of this study, there is a pattern of communication as an educational interaction between God and the Angels, between God and Satan, and between God and Adam AS and His Wife.